HYBRID POWER SYSTEM MODELING FOR ELECTRICITY SYSTEM IN SUMBAWA DISTRICT (HYBRID POWER SYSTEM MODELING) - sumartono -; Ahmad Agus Setiawan; Bertha Maya Sopha (Master in Systems Engineering, 2015)
Include the provision of energy management, utilization and enterprise shall be done justice, sustainability and so can not give optimal benefits for the greater welfare of the people. Sumbawa has a variety of potential sources of renewable energy such as; water energy, solar energy, wind energy, geothermal energy and biomass. From a variety of renewable energy potential can be made a model of hybrid power system design for the electrical system in Sumbawa is based on renewable energy in the region. The purpose of this study was to determine the magnitude of the potential of renewable energy for power generation, knowing large share of renewable energy to the electrical energy needs and design a model of hybrid power system for electrical system in Sumbawa by using HOMER (Hybrid Optimisation Model for Electric Renewables). The results of this study recommend a model of hybrid power system that is optimum for a total net present cost (NPC) US 144,954,400, operating cost of US 1,801,515 / year, the cost of electric (COE) US 0.090 / kWh of excess electricity and 99,072,760 (kWh / year) and the contribution of each component of the capacity modeling results are; PV Array 4.4%; wind turbine 20.3%; hydro turbine 74.4%; biomass generator 0.8%; G1 and G2 diesel generator as a back-up system by 0.1%. The results of model simulations also show that the model of hybrid power system that is recommended to have much lower levels of emissions than conventional systems where there is a reduction in the level of emissions into the environment by 99.75%. Thus the hybrid power system for electrical system in Sumbawa considered feasible as an alternative solution to meet the electrical energy needs in Sumbawa